ChemInform Abstract: Iron‐Catalyzed Trifluoromethylation of Enamide. Issue 29 (July 2015) - Rey‐Rodriguez, Romain; Retailleau, Pascal; Bonnet, Pascal; Gillaizeau, Isabelle
Abstract The first example of an Fe(II)‐catalyzed trifluoromethylation of enamides, e.g. (I), (IV), (VI), (VIII), and (X), using Togni′s reagent (II) as electrophilic CF3 source is reported.